Management of skin cancer by agonists of 5-HT1A and antagonists of 5-HT2A receptors - Menezes, Ana Catarina da Silva Fernandes Saraiva de (2015)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2015